“Impact of Ergonomics implementation on the Safety Culture: A Literature Overview” (International Journal of Food and Nutritional Sciences, 2022)
This research paper tries to establish a relationship between the ‘Ergonomics’ and the ‘Safety Culture’ variables specific to the Oil & Gas Industry in the Middle East region, by reviewing the related Research papers published in the same area.The model used is HSE Culture ladder by “International Association of Oil and Gas Producer” (OGP), the concept has supported by Hudson (2001) that define safety culture maturity model into 5 levels namely Pathological, Reactive, Calculative, Proactive and Generative.Literature review was done with the Research Papers, Safety Manuals and various other documents in the said field and several gaps were identified in the study which will form a base for the Research Study. It was observed that a lot of research has been done in allied areas, but no significant research is carried out in the area where effect of implementing Ergonomics is studied to show the improvement in the ‘Safety Culture’ of that organization.The major gaps identified were pertaining to developing new models, approaches and tools to integrate prevention of work-related injuries and diseases into the design process and also a need of analysis of the occupational hazards and accidents and ways to address them as a part of improving the ‘Safety Culture’ of the organization.